Cigarette smoke extract modulates E-Cadherin, Claudin-1 and miR-21 and promotes cancer invasiveness in human colorectal adenocarcinoma cells. (15th December 2019) - Dino, P.; D'Anna, C.; Sangiorgi, C.; Di Sano, C.; Di Vincenzo, S.; Ferraro, M.; Pace, E.
Highlights: Cigarette smoke is considered a risk factor for lung and colorectal cancer. Cigarette smoke induces epithelial mesenchymal transition features in Caco2. Cigarette smoke increases the invasive potential of Caco2. Abstract: Background: Cigarette smoke is considered a risk factor for lung and colorectal cancer. A convincing link between epithelial-to-mesenchymal transition (EMT) with colorectal cancer progression and therapeutic resistance has emerged. Deregulated expression of E-Cadherin and Claudin-1 and increased miR-21 expression and invasiveness represent hallmarks of EMT. The effects of cigarette smoke exposure on EMT in colorectal adenocarcinoma cells are largely unknown. Aim: The aim of the study is to evaluate the effect of cigarette smoke extract (CSE) on miR-21, Claudin-1 and E-Cadherin, molecules associated to EMT in colorectal cancer cells. Methods: A human colorectal adenocarcinoma cell line (Caco-2) was treated with CSE at different concentration (5% and 10%) and for different time points (3 h and 24 h). Metabolic activity (by MTS assay), cell necrosis/cell apoptosis (evaluating Propidium Iodide/Annexin V expression by flow cytometry), miR-21, Claudin-1 and E-Cadherin gene expression were evaluated by Real time PCR. Cell permeability, actin polymerization and cancer cell migration was assessed by Trans-Epitelial Electrical Resistance (TEER), Phalloidin expression and matrigel system, respectively. Results: CSE at all the tested concentrations and at all time points reduced cell necrosis. CSE at 10% increased miR-21 and reduced the metabolic activity, cell necrosis, Claudin-1 and E-cadherin mRNA at 3 h. Cell permeability, actin polymerization and cancer cell migration were all increased upon CSE exposure. Conclusion: These results showed that CSE increasing miR-21, Claudin-1 and E-Cadherin and enhancing the aggressiveness of cancer cells, may concur to colorectal cancer progression.